Association between blood pressure levels and cardiovascular deaths: a 20-year follow-up study in rural China. Issue 2 (25th February 2020) - Wang, Mengying; Wu, Tao; Yu, Canqing; Gao, Wenjing; Lv, Jun; Wu, Yiqun; Qin, Xueying; Tang, Xun; Gao, Pei; Zhan, Siyan; Cao, Weihua; Zhao, Qingshui; et al.
Abstract : Objectives: The 2017 American College of Cardiology/American Heart Association (ACC/AHA) hypertension guideline recommended 130/80 mm Hg as blood pressure (BP) target goals. However, the generalisability of this recommendation to populations at large with hypertension remains controversial. We assessed the association between BP and cardiovascular diseases (CVDs) mortality using a 20-year follow-up study among Chinese populations. Design: Prospective cohort study. Participants: 7314 participants were followed up for a median of 20 years in Fangshan District, Beijing, China. Methods: The primary outcome variable was death from cardiovascular causes. The adjusted HR for CVDs mortality associated with baseline BP was calculated using Cox regression analysis. Results: We identified 350 deaths from CVDs (148 stroke, 113 coronary heart disease and 89 other CVDs) during follow-up. Hypertension (defined by systolic BP (SBP)/diastolic BP (DBP) ≥140/90 mm Hg) was significantly associated with mortality due to CVDs (HR=2.49, 95% CI=1.77 to 3.50) among people aged 35–59 years rather than people aged ≥60 years. In addition, there was no significant association between stage 1 hypertension defined by the 2017 ACC/AHA (SBP/DBP of 130–139/80-89 mm Hg) and CVDs mortality when compared with SBP/DBP of <120/80 in neither the participants aged <60 years (HR=0.90, 95% CI=0.54 to 1.50) nor participants aged ≥60 years (HR=1.47, 95% CI=0.94 to 2.29). Conclusion: The study revealed hypertension of SBP/DBP≥140/90 mm Hg was an important risk factor of CVDs mortality, especially among people aged 35–59 years. However, stage 1 hypertension under the definition of 2017 ACC/AHA was not associated with an increased risk of CVDs mortality. This study indicated that whether adopting the new hypertension definition needs further consideration in rural Chinese populations.